Efficiency of B-Mode Ultrasound and Strain Elastography in Differentiating Between Benign and Malignant Cervical Lymph Nodes - Turgut, E.; Çelenk, C.; Tanrivermiş Sayit, A.; Bekci, T.; Günbey, Hediye Pınar; Aslan, K. (Lippincott Williams and Wilkins kathiest.clai@apta.org, 2017)
Purpose: The purpose of this study was to evaluate the diagnostic accuracy and efficiency of ultrasonography (US), especially when combined with strain elastography (SE), in differentiating between benign and malignant cervical lymph nodes (LNs). Methods: Forty-one LNs were examined by B-mode US, power Doppler US, and SE. The following imaging features were analyzed: Shape, echogenicity, echogenic hilum, calcification, intranodal vascular pattern, elasticity scores (5 categories), and strain ratio. The average strain ratio was calculated as the mean strain of the adjacent sternocleidomastoid muscle divided by the mean strain of the target LN. The results of the US and SE features were compared with the histopathologic findings. Results: The imaging features that were significantly associated with malignant LNs were an increased short-to-long axis diameter ratio, abnormal or absence of hilum, microcalcification, type 2-3-4 vascularity, 3-4-5 elasticity scores, and a high level of strain ratio (P < 0.05). The cutoff value of the strain index was detected as 1.18. According to this, there was a significant difference (P = 0.004) in the strain index between benign and malignant LNs. Conclusions: Strain elastography is useful in differentiating between benign and malignant cervical LNs, thereby informing decisions to perform a biopsy and/or surgery, and facilitating follow-up. © 2017 Wolters Kluwer Health, Inc.
Keywords: B-Mode US; Cervical Lymph Nodes; Power Doppler US; Strain Elastography